Practitioner research in early childhood international issues and perspectives - Newman, Linda; Woodrow, Christine (SAGE, 2015)
"Bringing together theory and practice, this book draws on the projects and experiences of senior and new researchers implementing various forms of practitioner research. Chapter discussions are informed by international literature to provide insightful reflections on research processes and the contribution of practitioner research to changing practice. The diversity of perspectives across the chapters provides an excellent resource for those undertaking research within early childhood contexts. Topics discussed include: the contribution of practitioner research to curriculum and social change; professional development and strengthening learning communities; how practitioners can be supported in documenting and articulating their work; the relationships between the research community and field of practice through practitioner research projects; contemporary problems and issues that frame the practices of early childhood educators; case studies from Australia, South Africa, Swede and Chile." -- Back cover.